2000
DOI: 10.1007/bf03018993
|View full text |Cite
|
Sign up to set email alerts
|

Gastric distension and ventilation during laparoscopic cholecystectomy: LMA-classic vs. tracheal intubation

Abstract: Purpose: The standard laryngeal mask airway LMA-Classic was designed as an alternative to the endotracheal tube (ETT) or the face mask for use with either spontaneous or positive pressure ventilation. Positive pressure ventilation may exploit leaks around the LMA cuff, leading to gastric distension and/or inadequate ventilation. We compared gastric distension and ventilation parameters with LMA vs ETT during laparoscopic cholecystectomy.Methods: One hundred and one, ASA I-II adults scheduled for elective lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
2
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 20 publications
(17 reference statements)
2
51
2
4
Order By: Relevance
“…Stomach size at insertion of the laparoscope and change in stomach size during surgery were similar in both groups. These results are similar to those in our previous study 7 in which we compared LMA-C vs ETT in non-obese patients and did not pass a gastric tube. The only statistically significant differences in this study were related to smoother emergence from anesthesia in the LMA-PS group.…”
Section: Me Et Th Ho Od Ds Ssupporting
confidence: 91%
See 2 more Smart Citations
“…Stomach size at insertion of the laparoscope and change in stomach size during surgery were similar in both groups. These results are similar to those in our previous study 7 in which we compared LMA-C vs ETT in non-obese patients and did not pass a gastric tube. The only statistically significant differences in this study were related to smoother emergence from anesthesia in the LMA-PS group.…”
Section: Me Et Th Ho Od Ds Ssupporting
confidence: 91%
“…In a previous study in non-obese patients undergoing laparoscopic cholecystectomy with PPV, 7 we confirmed that there were no clinically significant differences in pulmonary ventilation measurements or gastric distension between the LMA-C and ETT. In this study, we compared pulmonary ventilation measurements, gastric distension and emergence outcomes between the LMA-PS and ETT in non-obese and obese patients for laparoscopic cholecystectomy.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, we had previously shown that the LMA-C and ETT with PPV were equally effective during laparoscopic cholecystectomy in non-obese patients, when mean peritoneal insufflation time was 47 min. 7 The PLMA permitted higher airway pressures without leak in all obese patients, satisfactory pulmonary ventilation without clinically significant gastric distension, and use of basal or near-basal FGF. Our inclusion of obese patients with a history of GER may be controversial.…”
Section: Méthode : Nous Avons Réparti 209 Femmes $ 18 Ans D'état Phmentioning
confidence: 99%
“…Patients fasted according to current Canadian Anesthesiologists' Society Guidelines (minimum two hours after clear liquid, six hours after a light meal). 7 No sedative premedication was given unless requested by the patient.…”
Section: Méthode : Nous Avons Réparti 209 Femmes $ 18 Ans D'état Phmentioning
confidence: 99%